2009
DOI: 10.1007/s10389-009-0291-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary survey of the prevalence of allergic disorders in a questionnaire-based study in Boshroye, a rural area of Iran

Abstract: The susceptibility of 25 Stenotrophomonas maltophilia (S. maltophilia) clinical isolates to four different antimicrobials (trimethoprim/sulfomethoxazole, piperacillin/tazobactam, ceftazidime, ciprofloxacin) were investigated by disk diffusion, E-test and commercial Sensititre and PASCO broth microdilution techniques. Discrepancies between the results of broth microdilution and the other methods studied were characterized as very major, major and minor errors. Using the broth microdilution as the reference meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…Researchers demonstrated that hay fever symptoms have negative impact on quality of life (Linneberg et al 2002;Kiotseridis et al 2013). On the other hand, the relations of pollen and people have been predetermined by different socio-economical and geographical factors (Yamauchi et al 2009;Fereidouni et al 2010). Our study suggests that subjects have experienced the effects of allergenic pollen; however, it could be that these effects only minimally disturb their everyday and outdoor leisure activities.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Researchers demonstrated that hay fever symptoms have negative impact on quality of life (Linneberg et al 2002;Kiotseridis et al 2013). On the other hand, the relations of pollen and people have been predetermined by different socio-economical and geographical factors (Yamauchi et al 2009;Fereidouni et al 2010). Our study suggests that subjects have experienced the effects of allergenic pollen; however, it could be that these effects only minimally disturb their everyday and outdoor leisure activities.…”
Section: Discussioncontrasting
confidence: 48%
“…Impact of pollen on the quality of life is associated with both pollen load in a territory (Fereidouni et al 2010;Velasco-Jiménez et al 2014) and lifestyle (Kiotseridis et al 2013;Lâm et al 2014). Lithuania belongs to the group of countries in which pollen of It was demonstrated in the study carried out during 2013-2014 that pollen concentrations in adjacent years can be significantly different, and prevention of diseases associated with airborne pollen becomes more difficult due to this factor.…”
Section: Discussionmentioning
confidence: 98%
“…In case of allergic disorders, the prevalence of different allergic disorders in pregnant mothers is consistent with our previous surveys, and for asthma is in line with another study in Sabzevar, which is a city in the vicinity of Khorasan …”
Section: Discussionsupporting
confidence: 91%
“…maltophilia EUCAST set a breakpoint for TMP/SMX, even while the Clinical and Laboratory Standards Institute (CLSI) approved standards for levofloxacin, minocycline, ticarciline/calvulanate and ceftazidime. Then again, results obtained with TMP/SMX are the most reproducible, with no relation to the methods in susceptibility testing used [27]. In the Eastern and Southeast Europe, only data from Greece and Hungary are available [28, 29].…”
Section: Discussionmentioning
confidence: 99%